Burnout Phenomenon of Guidance and Counseling Millennial Teachers in Junior High School - Apsarie, Hanna Harsy; Ilfiandra, Ilfiandra; Budiamin, Amin (GUIDENA: Jurnal Ilmu Pendidikan, Psikologi, Bimbingan dan Konseling, 2022)
The research is based on the phenomenon of burnout experienced by the human services profession, especially beginners. The research aims to describe burnout in guidance and counseling millennial teachers born between 1982 and 2003 in Junior High School in Bandung. The approach of the research was quantitative with a survey design. The participants in the study consisted of the guidance and counseling millennial teacher population in Bandung in the number of 27 people. The instruments used in this research were adapted from the Counselor Burnout Inventory developed by Lee et al. (2007) with 18 valid items, and the Cronbach Alpha's was 0.927, in the form of an interval scale. The technical data analysis used parametric statistics to compare the mean scores. The research findings indicate that millennial guidance and counseling teachers at Junior High Schools in Bandung are at a medium level of burnout.